PEMBERDAYAAN IBU PKK MELALUI PENANAMAN TANAMAN OBAT KELUARGA DAN PEMBUATAN MINUMAN HERBAL PENDUKUNG PEMELIHARAAN KESEHATAN - Yurike Septianingrum; Ratna Yunita Sari; M Shodiq; Lono Wijayanti (Institut Kesehatan Yarsi Mataram, 2026)
Family medicinal plants (TOGA) are natural resources with great potential to support community health independently. Lack of community knowledge about utilizing TOGA as herbal drinks is a problem that needs to be addressed. This community service activity aims to improve residents' knowledge and skills in planting TOGA and processing it into immunity-boosting herbal drinks based on ginger (Zingiber officinale), lemongrass (Cymbopogon citratus), honey, and lime (Citrus aurantifolia). The methods used include counseling, live demonstrations, and planting practice as well as herbal drink preparation. The activity was carried out in Banyu Urip Village, Surabaya City, attended by 30 participants. The results showed a significant increase in participants' knowledge from an average pre-test score of 52.3 to 83.7 on the post-test. All participants were able to independently practice planting TOGA and making herbal drinks. The conclusion of this activity is that the TOGA-based community service program has proven effective in increasing community knowledge and skills in utilizing herbal plants to maintain body immunity